2012
DOI: 10.1097/01.asw.0000419404.44947.de
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Keratin-Based Wound Dressing in the Management of Wounds in a Patient with Recessive Dystrophic Epidermolysis Bullosa

Abstract: Recessive dystrophic epidermolysis bullosa is a rare, autosomal recessive blistering condition. The authors successfully treated a patient with a novel keratin-based dressing. Starting at 11 months, 1 hand and 1 foot of the patient was treated, and significant improvement was observed. Thereafter, keratin treatment was applied to both hands and feet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 4 publications
0
11
0
2
Order By: Relevance
“…Keratins can self-assemble and be crosslinked to produce porous or fibrous scaffolds [ 32 , 34 , 35 , 36 , 37 ]. In particular, keratin is widely used as a wound dressing or scaffold for skin regeneration [ 38 ], as keratin promotes cell adhesion or the proliferation of keratinocytes or fibroblasts [ 20 , 21 ]. Although keratin has poor mechanical properties, various studies have been conducted to improve mechanical strength, while having good cell affinity, through mixing with various biomaterials [ 39 , 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Keratins can self-assemble and be crosslinked to produce porous or fibrous scaffolds [ 32 , 34 , 35 , 36 , 37 ]. In particular, keratin is widely used as a wound dressing or scaffold for skin regeneration [ 38 ], as keratin promotes cell adhesion or the proliferation of keratinocytes or fibroblasts [ 20 , 21 ]. Although keratin has poor mechanical properties, various studies have been conducted to improve mechanical strength, while having good cell affinity, through mixing with various biomaterials [ 39 , 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kirsner et al. [17] reported that a combination of keratin solution and a gauze bandage shows a highly improved healing effect on wound sites. Paladini et al.…”
Section: Introductionmentioning
confidence: 99%
“…[5] After treatment, it was observed that the number of blisters and the epithelialization period of the eroded areas significantly decreased in areas subjected to keratin application. [5] After treatment, it was observed that the number of blisters and the epithelialization period of the eroded areas significantly decreased in areas subjected to keratin application.…”
mentioning
confidence: 99%